High yield synthesis of multi-walled carbon nanotubed from CaCO3 supported iron (III) nitrate catalyst - Nguyễn, Đức Dũng (Đại học Quốc gia Hà Nội, 2017)
Chapter 1: Introduction to carbon nanotubes materiaI. Chapter 2. Experimental and investigation methods. Chapter 3. Results and discussion